A review of environmental stressor monitoring strategies used in micro- and nanofabrication. (29th January 2007) - Handy, Rodney G.; Jackson, Mark J.; Handy, Mary J.; Lafreniere, Michael D.
Increased efforts in the area of micro- and nanofabrication techniques have resulted in additional challenges for those professionals in the area of environmental, occupational health and safety. These techniques produce various environmental stressors which, when exposed to in significant concentrations, may produce harmful health consequences for workers as well as detriments to the environment. Fortunately, suitable monitoring strategies have been developed in order to provide real-time data analyses for concentration profiles and exposure characterisations associated with these stressors. While the main impetus of the vast majority of employee exposure monitoring strategies has traditionally targeted airborne chemical contaminants, the field of micro- and nanofabrication requires additional emphasis in such areas as nanoparticle measurement/analysis and laser safety. This paper provides a review of the viable environmental monitoring and measurement strategies that could be applied in micro/ and nanofabrication activities.